COMPARATIVE EVALUATION OF RESULTS OF CAROTID ARTERY STENTING AND CAROTID ENDARTERECTOMY IN PATIENTS WITH HIGH SURGICAL RISK - E.D. SULTANOV; N.A. CHIGOGIDZE; D.D. SULTANOV; A.K. BARATOV (Avicenna Tajik State Medical University, 2023)
Objective: To study the immediate and long-term results of carotid artery stenting (CAS) and carotid endarterectomy (CEA) in patients with high surgical risk. Methods: 84 patients with combined lesions of carotid bifurcations and coronary arteries were examined. There were 55 men (65.6%), and 29 women (34.4%) aged 42-84 years (median age 64 years). Various comorbidities were identified in 52 (61.9%) patients. Patients were divided into two groups: those who underwent CAS (35) and CEA (49). The follow-up period after surgery was up to 30 days (early), and up to 8 years (long-term). A comparative assessment of perioperative complications and long-term results after CAS and CEA were carried out. Results: The identified cerebrovascular risk factors for the development of perioperative complications were identical in both groups: recent stroke, occlusion of the contralateral internal carotid artery (ICA), intracranial lesions, and anomalies of the circle of Willis. Other risks included psychoemotional stress (85%), risk of nerve damage, bleeding, angina III, and IV functional classes (53.5%). Although not statistically significant, noticeable differences were found in perioperative complications after CAS and CEA (14.3% vs. 28.6%, respectively, p>0.05). In the long term, there were no statistically significant differences between the CAS and CEA groups in terms of overall survival (97.2% versus 100%, respectively, p>0.05), transient ischemic attacks (2.8% versus 4.1%, respectively, p>0.05), development of non-fatal myocardial infarction (MI) (11.4% versus 12.2%, respectively, p>0.05), fatal MI (2.8% versus 0%, respectively). Conclusion: Analysis of the immediate results of CAS and CEA showed, although statistically insignificant, noticeable advantages of the first method in the overall frequency of perioperative complications (14.3% vs. 28.6%, p>0.05) in patients from the category of high surgical risk. According to the main criteria of long-term results of the two methods, there was also no statistically significant difference, which allowed us to consider the endovascular method of treatment as an alternative to the traditional surgical technique.